Numerical Investigation of Transient Flow Characteristics in a Centrifugal Compressor Stage with Variable Inlet Guide Vanes at Low Mass Flow Rates - Shuai Li; Yan Liu; Mohammad Omidi; Chuang Zhang; Hongkun Li (Energies, 2021)
This study numerically investigates the beneficial effects of positive pre-swirl on the aerodynamic performance and internal flow field in a centrifugal compressor stage with variable inlet guide vanes (VIGVs) at low mass flow rates. Four positions of VIGV are considered, including 0°, 30°, 45°, and 60° angle. The latter three positions of VIGV induce positive pre-swirl. Numerical results show that as positive pre-swirl increases, the aerodynamic performance curve of the stage moves in the low mass flow rate direction. In the three cases of positive pre-swirl, there was an improvement of approximately 9.95% of stall/surge margin greater than in conditions with no pre-swirl. The regulation of IGV can effectively improve the unstable flow of the compressor stage at low mass flow rates. A low frequency that has a great influence on the internal flow of the compressor stage is found, and the unstable flow caused by low frequency is analyzed by the combination of streamline distribution, spectrum analysis, vector, entropy increase, and modal decomposition method. Meanwhile, the modal decomposition method and flow field reconstruction techniques are used to investigate the coherent flow structures caused by low frequency under different guide vane openings.